2019
DOI: 10.1186/s12915-019-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced lipid dynamics and transcriptional programs in white adipose tissue

Abstract: Background In mammals, cold exposure induces browning of white adipose tissue (WAT) and alters WAT gene expression and lipid metabolism to boost adaptive thermogenesis and maintain body temperature. Understanding the lipidomic and transcriptomic profiles of WAT upon cold exposure provides insights into the adaptive changes associated with this process. Results Here, we applied mass spectrometry and RNA sequencing (RNA-seq) to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 109 publications
(148 reference statements)
5
84
1
Order By: Relevance
“…However, the overall concentrations of lipid classes in GLY‐injected muscle were only affected marginally by cold exposure. The alteration patterns of fatty acyl chains associated with TAGs in GLY‐injected muscles resembled BAT more than white adipose tissue 20,21 . Marcher et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall concentrations of lipid classes in GLY‐injected muscle were only affected marginally by cold exposure. The alteration patterns of fatty acyl chains associated with TAGs in GLY‐injected muscles resembled BAT more than white adipose tissue 20,21 . Marcher et al .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that by experimentally induced cold exposure, a shifting of intramuscular adipocytes towards a brown phenotype may be functionally related to some improvements in systemic metabolism. Cold exposure has been reported to be an efficient method to induce energy expenditure by activating UCP1 and influencing the dynamics of lipid metabolism and transcriptional processes in brown and white adipose tissue 20,21 . However, lipidomic alteration and its regulatory mechanism in the adipocyte‐infiltrated skeletal muscle remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there have been a few studies which have shown that inactivation of mTORC1 also compromises thermogenesis (D. Liu et al, 2016;Tran et al, 2016). While exposure to cold is also known to induce browning effect in mammals, it has been found to modify pathways involved in AD in a study carried out in mice models (Xu et al, 2019). Since mTOR and COX-2 have been found to operate together directly or indirectly in various other disorders or conditions, it can also be speculated that they may affect each other in this particular case.…”
Section: Cox-2 and Mtor In Cell Metabolism And Signaling Cascades: Immentioning
confidence: 99%
“…Epidemiological studies have linked diabetes and obesity with dementia ( Ferreira et al, 2018 ). In fact, a lot of recent studies have highlighted the common cellular pathways underlying both diabetes and AD, thereby coining the term “type-3-diabetes” or “brain diabetes” to refer to AD ( Xu et al, 2019 ). Anti-diabetic drugs are being explored as potential candidates of anti-AD therapy ( De Felice, 2013 ).…”
Section: Cox-2 and Mtor In Cell Metabolism And Signaling Cascades: Immentioning
confidence: 99%
“…Cold exposure induces beige fat biogenesis in subcutaneous white adipose tissue (scWAT) depots, promotes energy expenditure, and decreases mice body weight and fat mass (5). During cold exposure, β3-adrenergic receptor (β3AR) is activated by catecholamines released from sympathetic nerve.…”
Section: Introductionmentioning
confidence: 99%